THE INFLUENCE OF HIP JOINT CONTROL ON KNEE JOINT VALGUS MOMENT IN YOUNG FEMALE ELITE ATHLETES. Issue 7 (11th March 2014) - Bencke, J; Lauridsen, HB; Thorborg, K; Hölmich, P; Andersen, LL; Aagaard, P; Zebis, MK
Abstract : Background: Biomechanical investigations of sports-specific movements may yield information on which measures could be most efficient for prevention of Anterior Cruciate Ligament (ACL) injuries. High knee valgus moments have been related to increased risk of ACL injury, but further knowledge is needed on how hip strength and hip joint control may influence valgus moments during sidecutting. Objective: To investigate the relation between isolated hip muscle strength, hip kinematics and knee valgus moments. Design: Cross-sectional. Setting: Biomechanical laboratory. Youth elite level. Participants: 97 female handball and football players aged 15–19 yrs selected for the youth national teams were recruited. Assessment of risk factors: Maximal isometric hip strength was measured during hip abduction, hip extension and hip external rotation [N/kg BM]) by a handheld dynamometer. A standardized sidecutting was performed by each player and hip joint kinematics were measured at initial contact (IC) along with identification of the peak knee joint valgus moment in the contact phase. Main outcome measurements: Regression analysis was used to determine which of the measured parameters would affect knee valgus moment, and as such represent potential risk factors that should be targeted in future prophylactic training regimes. Results: No relation between maximal isometric hip muscle strength and knee valgus moment was found. Regression analysis showed weak but significant effect of hip internal rotation at IC and hip abduction at IC on knee valgus moment (r 2 =.33, P<.001, β-coefficients=0.49 and 0.35 for hip internal rotation and hip abduction, respectively). Conclusions: The study shows that isometric hip muscle strength did not relate to peak knee valgus moment in young female elite handball and football players. However, increased hip internal rotation and increased hip abduction appeared to negatively influence the magnitude of knee valgus moment during sidecutting, and thus potentially increase the risk of ACL-injury.